Clinical and electrophysiological findings in C9ORF72 ALS. Issue 3 (11th July 2022) - Sista, Sri Raghav S.; Shelly, Shahar; Oskarsson, Björn; Rubin, Devon I.; Martinez‐Thompson, Jennifer M.; Parra‐Cantu, Carolina; Staff, Nathan P.; Laughlin, Ruple S.
Abstract: Introduction/Aims: Amyotrophic lateral sclerosis (ALS) is a progressive, fatal, neurodegenerative disorder of motor neurons in which the cause is mostly unknown. Early identification of genetic ALS cases, of which C9ORF72 (C9ALS) is the most frequent, can have important implications for evaluation, prognosis, and therapeutics. Here, we aimed to characterize the clinical and electrophysiological hallmarks of C9ALS and investigate differences from C9ORF72 negative ALS (non‐C9ALS). Methods: We retrospectively reviewed clinical and electrodiagnostic (EDX) data for all genetically confirmed C9ALS cases seen between 1/1/2012 and 10/1/2020 who met Gold Coast criteria and compared them 1:1 with non‐C9ALS patients within the same time frame. Results: A total of 99 C9ALS and 99 non‐C9ALS cases were identified. Compared to non‐C9ALS, C9ALS demonstrated higher prevalence in women, lesser racial variability, stronger family history of ALS, and higher frequency of upper motor neuron signs. EDX testing of C9ALS showed higher median sensory nerve and lower fibular compound muscle action potential amplitudes. Discussion: Although the differences between C9ALS and non‐C9ALS reached statistical significance in certain nerve conduction parameters, they were not sufficient to discriminate between groups on a case‐by‐case basis. Genetic testing is required to identify C9ALS patients.